Can ablation win against partial nephrectomy and become first line therapy in cT1a renal tumours? - Sandbergen, Laura; Güven, Selçuk; del Pilar Laguna Pes, Maria (Lippincott Williams and Wilkins, 2019)
Purpose of review Currently, small renal masses account for the largest proportion of renal tumour and small renal cell carcinomas (RCC). Although partial nephrectomy, whenever possible, is recognized as the gold standard for treatment, thermal ablation has gained increasing attention as optional treatment in a population sector harbouring small renal masses/small RCCs. The purpose of this review is to update comparative outcomes between these two options of treatment. Recent findings Recent observational case-control and population-based cohorts applying propensity score or inverse probability treatment weighted methodology adjusting for baseline patient and tumour characteristics, compare outcomes between partial nephrectomy and thermal ablation (both cryotherapy and radiofrequency), radical nephrectomy and thermal ablation and between thermal ablation and nonsurgical management. Most of them focus on T1aRCC. Summary Comparative outcomes' evidence is limited to population-based or institutional series adjusted for baseline differences and systematic reviews. With exception of special clinical situations, thermal ablation provides similar estimated 5-year cancer and overall survival with a clear benefit in postoperative outcomes when compared to partial nephrectomy in cT1a older patients. The trade-off is more evident when thermal ablation is compared to radical nephrectomy. The advantages in terms of adverse events persist up to 1 year after treatment. Benefits are less apparent in solitary kidneys and when synchronous bilateral approaches are performed.
WOS: 000467768700011
PubMed ID: 30308573
Keywords: Cryoablation; CT1a Renal Mass; Localized Renal Mass; Minimally Invasive Surgery; Partial Nephrectomy; Percutaneous Ablation; Radiofrequency; Renal Cell Carcinoma; Robotic; Small Renal Masses; Thermal Ablation